Development of Islamic Religious Education Learning Media through 3D Animation for Grade VII at Muhammadiyah 57 Junior High School, Medan - Syahputra, Afit; Fajar, Muhammad; Lubis, Apdi (Yayasan Rahmat Islamiyah, 2025)
This study aims to develop 3D animation-based learning media for Islamic Religious Education subjects for seventh-grade students at Muhammadiyah 57 Junior High School, Medan. The background of this research is the lack of students' interest and motivation in learning abstract and non-visual Islamic Education materials. The method used in this study is Research and Development (RD) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results show that the developed 3D animation media is highly suitable for use in the learning process, with validation results from media experts at 92%, material experts at 88%, and student responses at 91%. This media helps students better understand the material visually, increases learning interest, and creates an interactive and enjoyable learning atmosphere.